Genetics of type II glycogenosis: Assignment of the human gene for acid α-glucosidase to chromosome 17 - D'Ancona, Gian G. (1979)
We have studied somatic cell hybrids between thymidine kinase (EC 2.7.1.75) deficient mouse cells and human diploid fibroblasts for the expression of human acid α-glucosidase (EC 3.2.1.20). A deficiency in this enzyme is associated with the type II glycogenosis or Pompe disease. All 30 somatic cell hybrids selected in hypoxanthine/aminopterin/thymidine medium expressed human acid α-glucosidase and galactokinase (EC 2.7.1.6) and retained human chromosome 17; counterselection of the same hybrids in medium containing 5-bromodeoxyuridine resulted in the growth of hybrids that concordantly lost the expression of human acid α-glucosidase and galactokinase as well as human chromosome 17. Hybrids between thymidine kinase-deficient mouse cells and fibroblasts from a patient with Pompe disease that contained human chromosome 17 were found not to express human acid α-glucosidase. Because we have already shown that hybrids between mouse peritoneal macrophages and GM54VA simian virus 40-transformed human cells selectively retain human chromosome 17 and lose all other human chromosomes, we tested 13 independent mouse macrophage × GM54VA hybrid clones, including two that retained human chromosome 17 and no other human chromosomes, for the expression of human acid α-glucosidase and galactokinase. All 13 hybrid clones were found to express these human enzymes. Thus, we conclude that the gene coding for human acid α-glucosidase is located on human chromosome 17.